Optimal particle distribution induced interfacial polarization in hollow double-shell composites for electromagnetic waves absorption performance - Cao, Xiaolong; Liu, Xuehua; Zhu, Jiahui; Jia, Zirui; Liu, Jinkun; Wu, Guanglei (Journal of colloid and interface science, 2023)
Enhanced electromagnetic wave absorption through the unique hollow double shell structure and the synergistic effect of dielectric loss magnetic and loss. [Display omitted] •CoS2 coated with metal-doped carbon was prepared by a soft template method and wet impregnation method.•The double-layer hollow shell structure is retained after the modification of metal nanoparticles.•Metal doping optimizes the electromagnetic wave loss mechanism of the material.•The RLmin is −48.90 dB at 2.23 mm, and the maximum Effective Absorption Bandwidth is 5.04 GHz at 1.98 mm. Tunable designs of polymorphic structured transition metal dichalcogenide (TMDC) demonstrate promising applications in the field of electromagnetic wave absorption (EMW). However, it remains a technical challenge for achieving a balanced relationship between well-matched impedance characteristics and dielectric losses. Therefore, the co-modification strategies of polydopamine coating and wet impregnation are chosen to construct CoS2 magnetic double-shell microspheres with phase component modulation to achieve the optimized performance. Dopamine hydrochloride forms a coating on the surface of CoS2 microspheres by self-polymerization and forms a double-shell structure during the pyrolysis process. Then the different metal is doped to generate heterogeneous components in the process of heat treatment. The results show that the cobalt doped double-shell microspheres have an ultra-high electromagnetic wave absorption absorption capacity with an effective absorption bandwidth of 5.04 GHz (1.98 mm) and a minimum reflection loss value of −48.90 dB. The double-shell layer structure and metal ion hybridization can improve the interfacial polarization and magnetic loss behavior, which provides an explicit inspiration for the development of transition metal dichalcogenide and even transition metal compounds with tunable absorption properties.